2016
DOI: 10.3390/pharmaceutics8020012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of P-Glycoprotein Inhibitory Potential Using a Rhodamine 123 Accumulation Assay

Abstract: In vitro evaluation of P-glycoprotein (P-gp) inhibitory potential is now a regulatory issue during drug development, in order to predict clinical inhibition of P-gp and subsequent drug–drug interactions. Assays for this purpose, commonly based on P-gp-expressing cell lines and digoxin as a reference P-gp substrate probe, unfortunately exhibit high variability, raising thus the question of developing alternative or complementary tests for measuring inhibition of P-gp activity. In this context, the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 50 publications
3
91
1
Order By: Relevance
“…Additional culture for two weeks in the same medium supplemented with 2% (vol/vol) DMSO was performed in order to get a full hepatocytic differentiation of the cells (Gripon et al 2002). P-gp overexpressing mammary MCF7R cells (Jouan et al 2016) and MRP2-expressing human hepatoma HuH-7 cells (Olsavsky et al 2007), were cultured in Dulbecco's modified Eagle medium (DMEM) (Life Technologies), supplemented with 10 % (vol/vol) fetal calf serum, 10 IU/mL penicillin and 10 µg/mL streptomycin. BCRP-transfected cells HEK 293 (HEK-BCRP cells) (Tournier et al 2010), kindly donated by Dr X. Decleves (Faculty of Pharmacy, University Paris-Descartes, Paris, France), were cultured in DMEM supplemented with 10% (vol/vol) fetal calf serum, 100 IU/mL amoxicillin, 100 µg/mL erythromycin and 2 mg/mL G418.…”
Section: Cell Culturementioning
confidence: 99%
“…Additional culture for two weeks in the same medium supplemented with 2% (vol/vol) DMSO was performed in order to get a full hepatocytic differentiation of the cells (Gripon et al 2002). P-gp overexpressing mammary MCF7R cells (Jouan et al 2016) and MRP2-expressing human hepatoma HuH-7 cells (Olsavsky et al 2007), were cultured in Dulbecco's modified Eagle medium (DMEM) (Life Technologies), supplemented with 10 % (vol/vol) fetal calf serum, 10 IU/mL penicillin and 10 µg/mL streptomycin. BCRP-transfected cells HEK 293 (HEK-BCRP cells) (Tournier et al 2010), kindly donated by Dr X. Decleves (Faculty of Pharmacy, University Paris-Descartes, Paris, France), were cultured in DMEM supplemented with 10% (vol/vol) fetal calf serum, 100 IU/mL amoxicillin, 100 µg/mL erythromycin and 2 mg/mL G418.…”
Section: Cell Culturementioning
confidence: 99%
“…17) Rhodamine 123 is a lipophilic cation that is selective for P-glycoprotein-dependent transport 18) and has been widely used as an in vitro and in vivo marker of P-glycoprotein function. [19][20][21][22] Jouan et al reported that rhodamine 123 could be used for the prediction of clinical P-glycoprotein inhibition according to the Food and Drug Administration (FDA) criteria, with notable sensitivity (80%). 23) For example, the National Cancer Institute of the United States uses rhodamine 123 to screen for drugs that serve as substrates for P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Jouan et al reported that rhodamine 123 could be used for the prediction of clinical P-glycoprotein inhibition according to the Food and Drug Administration (FDA) criteria, with notable sensitivity (80%). 23) For example, the National Cancer Institute of the United States uses rhodamine 123 to screen for drugs that serve as substrates for P-glycoprotein. 24) Van der Sandt et al reported rhodamine 123 is a substrate for both P-glycoprotein and the organic cation carrier systems in the kidney cell line.…”
Section: Discussionmentioning
confidence: 99%
“…P‐glycoprotein/ ABCB1 ‐overexpressing mammary MCF7R cells and multidrug resistance‐associated proteins (MRP/ ABCC )‐expressing human hepatoma HuH‐7 cells were cultured in Dulbecco's modified Eagle medium (DMEM; Life Technologies), supplemented with 10% (vol/vol) fetal calf serum, 20 IU/mL penicillin, and 20 μg/mL streptomycin. Breast cancer resistance protein (BCRP/ ABCG2 )‐transfected HEK293 cells (HEK‐BCRP cells), kindly donated by Pr X. Decleves (Faculty of Pharmacy, University Paris‐Descartes, Paris, France), were cultured in DMEM supplemented with 10% (vol/vol) fetal calf serum, 100 IU/mL amoxicillin, 100 μg/mL erythromycin, and 2,000 μg/mL G418.…”
Section: Methodsmentioning
confidence: 99%